Language Transformation: Tracing the Word Formation of Netspeak in the Digital Age - Sitorus, Nurhayati; Nasution, Khairina; Pujiono, Pujiono; Rangkuti, Rahmadsyah (Proceeding International Conference on Malay Identity, 2024)
In the digital era, communication through online platforms has undergone a significant transformation. This phenomenon gave birth to a new form of language called Netspeak, which reflects the way the younger generation communicates in cyber media. Netspeak is characterized by the simplification of language structures, the use of acronyms and abbreviations, and the replacement of words with symbols and numbers. In addition, the use of emojis and emoticons further enriches the variety of expressions used in online communication. This study aims to analyze and understand word formation process of Netspeak in cyber media. The approach used in this study is a qualitative approach with a virtual ethnography method. Data collection was carried out through full observation, screenshots, and diary routines without conducting interviews. After the data was collected, the data was analyzed using the Boellstorff concept, namely 1) systematizing data, 2) creating data thematization, and 3) narrating and building arguments. The results of the study shown that the word formation process found in this study includes acronyms, blending, clipping, borrowing, special symbols, combinations of symbols with numbers, combinations of letters with numbers, use of letter symbols as representations, derivation, reduplication, use of Emoticons or Emojis, use of capital letters and abbreviations which reflect the adaptive behavior of language users towards the need for fast and efficient communication.